(untitled) (Patan Prospective Journal, 2023)
Population growth, industrialization and other natural processes effects on air-pollution levels and climatic change. Atmospheric turbidity factors are an important parameter for assessing the air pollution. The main objective of this research is to study atmospheric turbidity factors on Pokhara (28.180° N, 83.970° E and 800 m asl), Nepal for a period of one year (2017). The daily data of aerosol optical depth (AOD) are derived from Aerosol Robotic Network (AERONET) of NASA. Daily, monthly and seasonal variation of atmospheric turbidity index are analyzed. The annual average of Angstrom exponential (α), Angstrom coefficient of turbidity (β) and Linked turbidity (LT) are found 1.2 ± 0.2, 0.19 ± 0.17 and 6.7 ± 3.4 respectively. The annual average of visibility is found 3.2 ± 2.5 km. Result of this research work is beneficial for the further identification, impact and analysis of atmospheric turbidity at different places with same geographical condition.